Proof: Entropy of the Poisson distribution
Index:
The Book of Statistical Proofs ▷
Probability Distributions ▷
Univariate discrete distributions ▷
Poisson distribution ▷
Shannon entropy
Metadata: ID: P486 | shortcut: poiss-ent | author: JoramSoch | date: 2025-02-06, 11:27.
Theorem: Let $X$ be a random variable following a Poisson distribution:
\[\label{eq:poiss} X \sim \mathrm{Poiss}(\lambda) \; .\]Then, the (Shannon) entropy of $X$ in nats is
\[\label{eq:poiss-ent} \mathrm{H}(X) = \lambda \left( 1 - \ln \lambda \right) + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \; .\]Proof: The entropy is defined as the probability-weighted average of the logarithmized probabilities for all possible values:
\[\label{eq:ent} \mathrm{H}(X) = - \sum_{x \in \mathcal{X}} p(x) \cdot \log_b p(x) \; .\]Entropy is measured in nats by setting $b = e$. Then, with the probability mass function of the Poisson distribution, we have:
\[\label{eq:poiss-ent-s1} \begin{split} \mathrm{H}(X) &= - \sum_{x \in \mathcal{X}} p(x) \cdot \log_e p(x) \\ &= - \sum_{x=0}^{\infty} \frac{\lambda^x e^{-\lambda}}{x!} \cdot \ln \frac{\lambda^x e^{-\lambda}}{x!} \\ &= - e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} \left[ \ln \lambda^x + \ln e^{-\lambda} - \ln x! \right] \\ &= - e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln \lambda^x}{x!} - e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln e^{-\lambda}}{x!} + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \\ &= - e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x x \cdot \ln \lambda}{x!} - e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x (-\lambda) \cdot \ln e}{x!} + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \\ &= - e^{-\lambda} \ln \lambda \sum_{x=0}^{\infty} \frac{\lambda^x \cdot x}{x!} + e^{-\lambda} \lambda \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \; . \end{split}\]Using the relation $x!/x = (x-1)!$, the first term can be developped as follows
\[\label{eq:poiss-ent-term1} \begin{split} e^{-\lambda} \ln \lambda \sum_{x=0}^{\infty} \frac{\lambda^x \cdot x}{x!} &= e^{-\lambda} \cdot \ln \lambda \cdot \sum_{x=0}^{\infty} \lambda \cdot \frac{\lambda^x}{\lambda} \cdot \frac{x}{x!} \\ &= e^{-\lambda} \cdot \lambda \cdot \ln \lambda \cdot \sum_{x=0}^{\infty} \frac{\lambda^{x-1}}{(x-1)!} \\ &= e^{-\lambda} \cdot \lambda \cdot \ln \lambda \cdot \left( \frac{\lambda^{-1}}{(-1)!} + \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} \right) \\ &= e^{-\lambda} \cdot \lambda \cdot \ln \lambda \cdot \left( \frac{1}{\lambda} \cdot \frac{0}{0!} + \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} \right) \\ &= e^{-\lambda} \cdot \lambda \cdot \ln \lambda \cdot \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} \; , \end{split}\]such that equation \eqref{eq:poiss-ent-s1} becomes
\[\label{eq:poiss-ent-s2} \mathrm{H}(X) = - e^{-\lambda} \lambda \ln \lambda \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} + e^{-\lambda} \lambda \sum_{x=0}^{\infty} \frac{\lambda^x}{x!} + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \; .\]Using the power series form of the exponential function
\[\label{eq:exp-sum} e^x = \sum_{n=0}^{\infty} \frac{x^n}{n!} \; ,\]equation \eqref{eq:poiss-ent-s2} finally becomes
\[\label{eq:poiss-ent-s3} \begin{split} \mathrm{H}(X) &= - e^{-\lambda} \lambda \ln \lambda e^{\lambda} + e^{-\lambda} \lambda e^{\lambda} + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \\ &= - \lambda \ln \lambda + \lambda + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \\ &= \lambda \left( 1 - \ln \lambda \right) + e^{-\lambda} \sum_{x=0}^{\infty} \frac{\lambda^x \ln x!}{x!} \; . \end{split}\]∎
Sources: Metadata: ID: P486 | shortcut: poiss-ent | author: JoramSoch | date: 2025-02-06, 11:27.